Modeling physical hypermedia applications - Gordillo, Silvia Ethel; Rossi, Gustavo Héctor; Lyardet, Fernando Daniel (2005)
In this paper we present a modeling approach for building physical hypermedia (PH) applications, i.e. those applications in which real and digital objects are navigated using the hypertext paradigm. We first survey the state of the art in this kind of ubiquitous applications. We stress the importance of modeling and design activities and present our design approach, an extension of the well-known Object-Oriented Hypermedia Design Method (OOHDM); we finally discuss some further work we are pursuing in this area.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
Proceedings of the International Workshop on Cyberspace Technologies and Applications, 410-414 January 2005.
Keywords: APLICACIONES WEB; HIPERMEDIA FÍSICA; MODELADO DE SOFTWARE